Prilling as an Effective Tool for Manufacturing Submicrometric and Nanometric PLGA Particles for Controlled Drug Delivery to Wounds: Stability and Curcumin Release - Chiara De Soricellis; Chiara Amante; Paola Russo; Rita Patrizia Aquino; Pasquale Del Gaudio (Pharmaceutics)
Background/Objectives: This study investigates for the first time the use of the prilling technique in combination with solvent evaporation to produce nano- and submicrometric PLGA particles to deliver properly an active pharmaceutical ingredient. Curcumin (CCM), a hydrophobic compound classified under BCS (Biopharmaceutics Classification System) class IV, was selected as the model drug. Methods: Key process parameters, including polymer concentration, solvent type, nozzle size, and surfactant levels, were optimized to obtain stable particles with a narrow size distribution determined by DLS analysis. Results: Particles mean diameter (d50) 316 and 452 nm, depending on drug-loaded cargo as Curcumin-loaded PLGA nanoparticles demonstrated high encapsulation efficiency, assessed via HPLC analysis, stability, and controlled release profiles. In vitro studies revealed a faster release for lower drug loadings (90% release in 6 h) compared to sustained release over 7 days for higher-loaded nanoparticles, attributed to polymer degradation and drug-polymer interactions on the surface of the particles, as confirmed by FTIR analyses. Conclusions: These findings underline the potential of this scalable technique for biomedical applications, offering a versatile platform for designing drug delivery systems with tailored release characteristics.